Would I ever use a Mac computer? - Muhammed Ramiza, Ramli (Faculty of Computer Systems and Software Engineering, 2011)
Know the Macintosh.Would I ever use a Mac Computer? Or would you? Absolutely! Every body should use Macintosh. As everybody who tries to use it will turn to love it. Maybe everybody has been using a computer for quite of time. And most of the time it is Microsoft Window based operating systems.